One more rep! The case for resistance training in young cancer survivors - Lakicevic, Nemanja; Ficarra, Salvatore; Ortega-Gómez, Sonia; Jiménez-Pavón, David; Asimakopoulou, Zoi; Vantarakis, Apostolos; Tavares, Paula; Vaz, Vasco; Thaller, Joshua; Papakonstantinou, Sofia; Kirkar, Musa; Glorioso, Francesca; et al. (Frontiers in Oncology, 2023)
Resistance training is now seen as a powerful tool to improve the health and functionality of cancer survivors. Literature shows that it can be implemented both during and after cancer treatment, with the intent of preserving muscle mass in the former and increasing muscle mass in the latter case. However, currently available data on this matter are predominantly derived from adult cancer survivors (ACS), and it is questionable whether the exact same raining regimen should be implemented in young cancer survivors (YCS) given the unique challenges they experience throughout their disease trajectory. Therefore, the goal of this work is to distill the existing evidence on resistance training (RT) interventions in ACS and facilitate discussion on whether the same patterns of RT can be applied in YCS.